Development of a Web-based Geographic Information System for Locating Medical Practices - Aman, Andryanto; Wisda, Wisda; Syamsu, Suryadi; Nasir, Khaidir Rahman; Maslihatin, Tatik; Iqlimah, Magfirah Nur (Ceddi Journal of Information System and Technology (JST), 2023)
This research aims to develop a Decision Support System (DSS) that can assist in selecting the best bus for tourism purposes in Toraja. The objective of this research is to facilitate the decision-making process for prospective tourists who want to use buses as their means of transportation during their visit to Toraja. The method employed in this research is the Weighted Product (WP) method. This method was chosen due to its ability to handle multiple criteria, enabling selection based on various relevant factors such as price, service quality, bus capacity, operational schedule, and level of comfort. Furthermore, the collected data will be input into the developed DSS using the WP method. The DSS will calculate relative scores for each bus based on the predetermined criteria weights. The results of this research are expected to provide objective and accurate recommendations for selecting the best bus. These recommendations can serve as a guide for prospective tourists in choosing a bus that suits their needs and preferences. Additionally, this research can also provide valuable insights for bus operators in improving service quality and customer satisfaction.